Kandungan Nitrogen, Phosphor, Kalium, dan pH Pupuk Organik Cair dari Sampah Buah Pasar Berdasarkan Variasi Waktu - Mailola Anli Kusumadewi; Adib Suyanto; Bambang Suwerda (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Traditional markets produce almost 95% of organic waste. At Gemah Ripah fruit market, the activity of transporting until the storage yields fruit waste, that if is not processed properly will cause many negative impacts. One way to utilize organic waste is process it as liquid organic fertilizer.The aim of this research is to study the difference of N, P, K and pH content of the liquid organic fertilizer made from different fermentation times. The study was an experiment with post test only group design. The study sample was 30 kg fruit waste, taken from 31 traders of Gemah Ripah fruit market in Gamping Sleman. The treatment was consisted of two fermentation time, i.e.1 week and 2 weeks, which were carried out in five replications. The results showed that the two fermentation times gave different levels of N, P, K and pH values, i.e. Nitrogen 0.43%; Phosphorus 0.15%; Potassium 0.27%; pH 6.9 for one week fermentation time, and Nitrogen 0.49%; Phosphorus 0.13%; Potassium 0.22%; pH 6,8 for two week fermentation time. Nitrogen content of the two weeks time is 0,06% higher; phosphorus content of one week time is 0,04% higher; and potassium content of one week time is 0,05% higher. It can be concluded that different fermentation time affect the N, P, K, and pH content of liquid organic fertilizer yielded from fruit market waste.